Mali : Technical Assistance Report-Audit of the Expenditure Chain. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses key findings of the Technical Assistance report on Mali. The expenditure chain in Mali is vulnerable, even though it is organized along traditional lines and is subject to a number of controls. The process establishes the separation of the payment authorization officer and accountant and includes numerous exante verifications. The Auditor General identified shortfalls in the amount of CFAF 35 billion, or a little more than 3 percent of the 2012 budget, in 17 audits conducted. This report also focuses on the expenditure chain and its complexities and weaknesses, and makes 10 practical recommendations.